2016
DOI: 10.3904/kjim.2015.198
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycemic control is associated with the risk of subclinical hypothyroidism in patients with type 2 diabetes mellitus

Abstract: Background/Aims:Overt hypothyroidism is frequently found in patients with type 2 diabetes mellitus (T2DM), but it remains unknown the relationship between subclinical hypothyroidism (SCH) and T2DM. We attempt to evaluate the difference in prevalence of SCH between patients with T2DM and general population, and the association between SCH and glycemic control status ofdiabetic patients.Methods:This was cross-sectional study. Total 8,528 subjects who visited for health check-up were recruited. SCH was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
3
19
2
3
Order By: Relevance
“…34,35 This could be due to the high prevalence of thyroid disorders among Keralites making them extremely common among T2DM patients when compared to other complications of DM. 36 Significantly higher participants who did not attain ADA glycemic goal had overt hypothyroidism which is similar to previous reports suggesting altered thyroid hormones in participants with poor glycemic control 37 which is thought to be due to abolition or blunting of nocturnal TSH peak and reduced response of TSH to TRH and due to the impairment of peripheral conversion of T4 to T3 which normalizes with glycemic control.…”
Section: Discussionsupporting
confidence: 84%
“…34,35 This could be due to the high prevalence of thyroid disorders among Keralites making them extremely common among T2DM patients when compared to other complications of DM. 36 Significantly higher participants who did not attain ADA glycemic goal had overt hypothyroidism which is similar to previous reports suggesting altered thyroid hormones in participants with poor glycemic control 37 which is thought to be due to abolition or blunting of nocturnal TSH peak and reduced response of TSH to TRH and due to the impairment of peripheral conversion of T4 to T3 which normalizes with glycemic control.…”
Section: Discussionsupporting
confidence: 84%
“…A study shows prevalence of 18.3% of SH in patients with Type 2 diabetes mellitus. The prevalence was found more in patients with age more than 50 years [45].…”
Section: Discussionmentioning
confidence: 83%
“…It is reported that the prevalence of hypothyroidism in diabetics varies from 0.2% to 1.7% [10]. However, a cross-sectional study showed that the prevalence of SCH was similar between patients with diabetes mellitus and healthy controls [11]. Therefore, we analysed molecular characters in patients with SCH (S), patients with SCH complicated with type 2 diabetes (SD), and healthy controls (N) by transcriptome sequencing to explore whether type 2 diabetes was associated with SCH.…”
Section: Introductionmentioning
confidence: 93%